Evaluation of the efficacy of oral metronidazole versus clindamycin in preventing preterm birth, maternal and fetal complication in patients with asymptomatic bacterial vaginosis - Zainal, NZ; Nirmala, CK; Jamil, MA (Wiley-Blackwell, 2024)
Indexed by WOS